A hybrid vibration mitigation method based on the crowd flow control and tuned mass damper on a footbridge. (15th October 2021) - Zhu, Qiankun; Yang, Wenbin; Zhang, Qiong; Du, Yongfeng
Highlights: The social force model for simulating the detour behaviour. A virtual three dimensional obstacle for crowd flow control. The time-varying coupling model of crowd-structure-TMD is established. The hybrid mitigation method for improving performance of vibration control. Factors analysis for determining mitigation rate. Abstract: This study proposes a hybrid mitigation method based on the crowd flow control and the eddy current tuned mass damper to control the excessive vibration caused by the random crowd excitation. The vibration mitigation method is applied on an experimental footbridge under random crowd loads and then the mitigation performance is analyzed experimentally and numerically. The numerical method of the social force model is used to simulate pedestrians detour behaviour in a blocking scenario. The time-varying coupling model of the crowd-structure-tuned mass damper is established, and the structure response is investigated. A virtual three dimensional obstacle based on the pedestrian stereo vision on the laboratory footbridge is designed to avoid the accident that pedestrians may encounter caused by the actual obstacles. It was found that the numerical response is in an appropriate agreement with the experimental data, implying that the social force model can simulate the detour behaviour accurately. Finally, the mitigation strategies are numerically implemented on an indoor footbridge, and the factors influencing the vibration mitigation rate are further analyzed using three different layouts. The layouts include Layout 1, for forcing pedestrian diversion separation, and Layout 2, for generating a bottle neck effect, and Layout 3, a nonlinear layout mode of obstacles, which is a combination of Layouts 1 and 2. The results show that the performance of the proposed hybrid mitigation method is more effective than the single mitigation method. In addition, the results show that the number and layout of obstacles determine the mitigation efficiency. It was also found that the vibration mitigation rate of the hybrid method with Layout 3 increases with the crowd density and tends to be stable when the crowd density exceeds 0.92 ped./m 2 . In addition, the mixed layout scheme may have more advantages in controlling crowd motion under high crowd density, while the linear layout schemes have certain competitiveness under low crowd density.